Profitabilitas, Struktur Modal, Ukuran Perusahaan, dan Kebijakan Dividen terhadap Nilai Perusahaan di BEI - Yudha Aru Putra Aru; ListyoriniWahyu Widati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This research was aimed to investigate the effect of profitability, capital structure, firm size, and dividend policy on firm value. Measurement of firm value in this research used price to book value (PBV). This research used manufacturing companies of food and beverages industry listed on Indonesian Stock Exchange for periode 2016-2020. The sample selection method used purposive sampling technique and obtained 44 samples. The data analysis used multiple linear regression test with SPSS 25 were used to analyze data. The result of analysis showed that capital structure, firm size and dividend policy has no effect on firm value. On the other side, profitability has significant positive effect on firm value.